High-energy, narrowband, non-resonant PPKTP optical parametric oscillator - Boyko, Andrey A.; Wang, Li; Mhibik, Oussama; Divliansky, Ivan B.; Zukauskas, Andrius; Moelster, Kjell; Chen, Weidong; Glebov, Leonid B.; Pasiskevicius, Valdas; Petrov, Valentin (Proceedings of SPIE)
We present a narrowband, non-resonant optical parametric oscillator based on 5-mm thick Rb-doped periodically-poled KTiOPO4 (PPKTP) operating in the high-energy/low repetition-rate regime. An uncoated volume Bragg grating (VBG) is employed as one of the cavity mirrors reflecting only the signal whereas the other cavity mirror is reflecting only the idler. Pumping by a Nd:YAG laser at 1.0642 mu m in a double-pass, the signal plus idler output energy reached almost 5 mJ at a repetition rate of 100 Hz corresponding to a conversion efficiency of similar to 26%. Both signal and idler are narrowband with full width at half maximum (FWHM) of 0.5 nm at 1942 nm and 0.76 nm at 2355 nm, respectively.